Surgical activity during the Covid-19 pandemic: Results for 112 patients in a French tertiary care center, a quality improvement study. (August 2020) - Philouze, P.; Cortet, M.; Quattrone, D.; Céruse, P.; Aubrun, F.; Dubernard, G.; Mabrut, J.Y.; Delignette, M.C.; Mohkam, K.
Abstract: Background: After the emergence of Covid-19 in China, Hubei Province, the epidemic quickly spread to Europe. France was quickly hit and our institution was one of the first French university to receive patients infected with Sars-COV2. The predicted massive influx of patients motivated the cancellation of all elective surgical procedures planned to free hospitalization beds and to free intensive care beds. Nevertheless, we should properly select patients who will be canceled to avoid life-threatening. The retained surgical indications are surgical emergencies, oncologic surgery, and organ transplantation. Material and methods: We describe the organization of our institution which allows the continuation of these surgical activities while limiting the exposure of our patients to the Sars Cov2. Results: After 4 weeks of implementation of intra-hospital protocols for the control of the Covid-19 epidemic, 112 patients were operated on (104 oncology or emergency surgeries and 8 liver transplants). Only one case of post-operative contamination was observed. No mortality related to Covid-19 was noted. No cases of contamination of surgical care personnel have been reported. Conclusion: We found that the performance of oncological or emergency surgery is possible, safe for both patients and caregivers. Highlights: During Covid-19 pandemic, we should properly select patients to avoid a life threatening. Need to continue surgical activities while limiting the exposure to the Sars Cov2. With all preventive actions, no mortality related to Covid-19 was noted. With all preventive actions, no cases of contamination of surgical care personnel.